PERSPEKTIF KOMPILASI HUKUM ISLAM: STATUS ANAK ADOPSI DALAM HUKUM KEWARISAN DAN WASIAT - Herman Beroni, herlina (Jurnal Landraad, 2023)
The distribution of inheritance frequently gives rise to disagreements, particularly when it comes to fairness, reliability, accountability, and openness. When adopted children are involved in the inheritance process, issues arise. The goal of this study is to identify patterns and types of distribution  of inheritance in adopted children in accordance with the Islamic Sharia laws found in the Compilation of Islamic Law. Through descriptive explanation and a qualitative methodology, this study measures and analyzes data. Case studies and phenomenology are two categories of study methods. This research is categorized as both library and field research based on where it was conducted. The conclusions of this study pertain to the pattern of distribution that the heir must create while still alive in the form of a legally required will with the distribution. based on the guidelines and regulations set forth in the Compilation of Islamic Law (HKI). Regarding the structure of inheritance in accordance with the division prescribed by the Koran and reinforced by the KHI.A necessary will must specify how much of the heir's estate can be given to adopted children; ideally, all that is specified in the form of a will with the heirs' awareness. This attempts to prevent misunderstandings between family members, which will ultimately lead to the filing of a case in court. Keywords: Adopted Children, Inheritance, Compilation of Islamic Law. Abstrak Sering kali terjadi perselisihan pembagian harta waris, khususnya berkaitan dengan keadilan, amanah,transparan dan akuntabel. Permasalahan berkembang dengan adanya keberadaan anak adopsi dalam pembagian harta waris. Penelitian ini bertujuan  untuk menemukan pola dan bentuk pembagian harta waris pada anak adopsi sesuai ketentuan syariah Islam dan termaktub  dalam Kompilasi Hukum Islam. Penelitian ini mengukur dan menganalisis  data dengan pendekatan kualitiatif melalui eksplanasi deskriptif. Tipe dan strategi penelitian tergolong Studi kasus dan Fenomenologi. Dilihat berdasarkan tempat, penelitian ini tergolong Library dan  Field Research. Penelitian ini menghasilkan temuan mengenai pola pembagian harta warisan harus dirancang sedemikian rupa oleh pewaris sewaktu masih hidup dalam bentuk wasiat wajibah dengan pembagian sesuai ketentuan dan aturan yang termuat dalam Kompilasi Hukum Islam (HKI). Adapun bentuk harta waris sesuai pembagian yang diatur dalam Alquran dan diperkuat pada KHI. Pemberian harta warisan kepada anak adopsi melalui wasiat wajibah tidak boleh melebihi sepertiga dari harta peninggalan pewaris dan sebaiknya segala sesuatu yang dituangkan dalam bentuk surat wasiat sepengetahuan ahli waris. Hal ini bertujuan untuk menghindari kesalah pahaman  antar anggota keluarga yang pada akhirnya terjadi acara gugat menggugat di pengadilan.   Kata kunci: Anak Adopsi,  Harta Waris, Kompilasi Hukum Islam.